Деякі напрями використання міжнародного досвіду правоохоронними органами системи МВС України - Голуб, М. В. (НДІ ПЗІР НАПрН України, 2022)
У статті розглянуті питання щодо необхідності використання досвіду роботи правоохоронних органів країн Європейського Союзу та США відповідними інституціями системи Міністерства внутрішніх справ України. Акцентовано увагу на тому, що за умов дії правового режиму воєнного стану правоохоронні структури України виконують завдання, пов’язані з відбиттям збройного нападу рф, а також забезпеченням недоторканості кордонів держави, підтриманням належного стану публічного порядку і безпеки, виявленням проявів колабораціонізму на підконтрольних територіях. В умовах дії на території України правового режиму воєнного стану від правоохоронних органів системи МВС України повинна бути максимально ефективна робота як результат використання всіх можливостей і напрацювань і, в тому числі, використання досвіду роботи правоохоронних органів країн-партнерів. Саме це питання є предметом цього дослідження. У статті проаналізовано досвід організації роботи правоохоронних органів у США та країнах Європи. Розглянуто методи вирішення проблемних питань щодо охорони публічного порядку, забезпечення безпеки населення у разі надзвичайних ситуацій та техногенних катастроф, протидії нелегальній міграції, охорони державного кордону, які використовуються у країнах-партнерах. Розглянуто засоби взаємодії поліції з місцевими органами виконавчої влади, місцевого самоврядування, громадськими організаціями та населенням. Запропоновано заходи підвищення ефективності функціонування Національної поліції, а також інших правоохоронних органів системи МВС України, використовуючи міжнародний досвід роботи правоохоронних структур країн Європи та США. Такими заходами, зокрема, можуть бути створення та відродження в Україні підрозділів муніципальної поліції, з урахуванням досвіду попередньої роботи таких підрозділів. Розглянуто принципи функціонування підрозділів муніципальної поліції в Німеччині, Франції, Великобританії, країнах Балтії, інших Європейських державах. Підкреслено необхідність впровадження позитивного досвіду роботи правоохоронних органів країн-партнерів України. Problem setting. Today, Ukraine is in a state of war. Active hostilities continue in some regions. Law enforcement agencies subordinate to the Ministry of Internal Affairs occupy one of the decisive positions in countering the aggressive manifestations of the Russian Federation. Law enforcement structures have a double burden, namely: performing tasks related to repelling an armed attack of the Russian Federation, as well as ensuring the inviolability of state borders, maintaining a proper state of public order and security, and detecting manifestations of collaborationism in controlled territories. Under the conditions of the legal regime of martial law on the territory of Ukraine, law enforcement agencies of the Ministry of Internal Affairs of Ukraine effectively perform tasks in all areas of official activity. We are talking about the maximum use of all opportunities and developments, including the use of the experience of law enforcement agencies of partner countries. In view of this, there is an urgent need to implement the positive experience of the law enforcement agencies of the USA and European countries. Analysis of recent researches and publications. Questions regarding the use of the experience of the police of Europe, the United States, and Japan in the field of security and public order protection at the national, regional, and local levels were investigated by domestic and foreign scientists, namely: O.M. Bandurka, O.I. Bezpalova, O.V. Jafarova, A.M. Dovgopolov, V.O. Zarosylo, N.V. Kaminska, V.L. Kostyuk, S.P. Melnyk, O.S. Pronevich, Yu.I. Rymarenko, V.O. Sichkar, E. Thompson, V.L. Filstein, O.S. Yunin, O.N. Yarmysh In these publications of scientists, the need to take into account the experience of the law enforcement system of foreign countries when introducing new forms and methods of work of law enforcement bodies of the system of the Ministry of Internal Affairs of Ukraine is substantiated. Target of the research is to investigate and analyze the actions of the National Police, as well as other law enforcement agencies of the Ministry of Internal Affairs of Ukraine, which are aimed at using international experience in the process of increasing the efficiency of the work of these state institutions. Study the experience of law enforcement agencies of EU countries and other foreign countries regarding measures aimed at ensuring the proper state of public safety and public order protection. Article’s main body. The article analyzes proposals for improving the effectiveness of the National Police, as well as other law enforcement agencies of the Ministry of Internal Affairs of Ukraine, using the international experience of law enforcement structures in Europe and the United States. Including the interaction of the police with local bodies of executive power, local self-government, public organizations and the population. Conclusions and prospects for the development. We can note that the effective functioning of the law enforcement system of independent Ukraine requires the leadership of the Ministry of Internal Affairs to implement the positive experience of the law enforcement agencies of the USA and European countries. as an example of such experience, in particular in the field of protection of human rights and freedoms, combating crime, protection of public order and security, in conditions of martial law, in our opinion, it is necessary, in particular, to develop proposals at the legislative level that provide for stricter responsibility of the participants and, in the first place in turn, the organizers of mass events for violating the order of their holding provided by law, including criminal liability (examples of EU countries).
Keywords: воєнний стан; досвід країн-партнерів; конституційні права і свободи; публічний порядок і безпека; зарубіжні правоохоронні органи; міжнародна взаємодія; співпраця; martial law; experience of partner countries; constitutional rights and freedoms; public order and security; foreign law enforcement agencies; international interaction; cooperation